Bioprocess Design: Fermentation Strategies for Improving the Production of Alginate and Poly-β-Hydroxyalkanoates (PHAs) by Azotobacter vinelandii - Peña, Carlos; Castillo, Tania; Núñez, Cinthia; Segura, Daniel (IntechOpen, 2011)
None